ON THE 125TH ANNIVERSARY OF ACETYLSALICYLIC ACID - I. N. Bokarev; L. V. Popova (Рациональная фармакотерапия в кардиологии, 2016)
An experience of acetylsalicylic acid (ASA) clinical use since its synthesis in 1887 is highlighted. ASA modes of action and its position among the modern antiplatelet agents are considered. The evidence based clinical data on ASA treatment and the problem of antiplatelet therapy resistance are discussed. ASA interaction with other drugs and ASA pleiotropic effects are reviewed